Labour Market in Crisis: The Moral Economy and Redundancy on the Upper Clyde, 1969–72. Issue 1 (April 2022) - Phillips, Jim
Abstract : The Upper Clyde Shipbuilders (UCS) work-in of 1971–2 is examined here within a moral-economy analysis of the longer history of deindustrialisation. Working-class expectations of security and voice in Scotland were cultivated by the management of industrial job losses from the late 1950s onwards. Labour governments were more trusted custodians of this moral economy than Conservative governments. Edward Heath's Conservative government, elected in 1970, violated the moral economy by allowing unemployment to accelerate, with particularly punishing effects in Glasgow. A labour market crisis materialised in 1970 before UCS went into liquidation in 1971. This article revisits an academic survey of men who took voluntary redundancy from UCS in 1969 and 1970, before market conditions deteriorated. Their unexpected experience of downward occupational mobility transgressed the moral economy and was a previously-unremarked factor in the mobilisation of the work-in against further job losses. The episode widened the political gulf between Scotland and England. Conservative policy-makers were discredited in working-class communities in Scotland before Margaret Thatcher and her governments embarked on their reckless management of deindustrialisation from 1979.